Effects of Intratympanic Dexamethasone on High-Dose Radiation Ototoxicity In Vivo. Issue 2 (February 2017) - Dinh, Christine T.; Chen, Si; Dinh, John; Goncalves, Stefania; Bas, Esperanza; Padgett, Kyle; Johnson, Perry; Elsayyad, Nagy; Telischi, Fred; Van De Water, Thomas
Abstract : Background: Stereotactic radiosurgery for lateral skull base tumors can cause hearing loss when the cochleae are exposed to high doses of single-fraction radiation. Currently, there are no known nondosimetric preventative treatments for radiation-induced ototoxicity. Hypothesis: Intratympanic (IT) dexamethasone (DXM), a synthetic steroid, protects against radiation-induced auditory hair cell (HC) and hearing losses in rats in vivo. Methods: Seven rats received radiation (12 Gy) to both cochleae. In irradiated rats and six nonirradiated rats, IT DXM was randomized to one ear, while tympanic puncture without DXM was performed on the contralateral ear. Baseline and 4-week postradiation auditory-evoked potential tests were performed. The cochleae were processed for HC viability. Results: Cochleae exposed to radiation demonstrated more outer HC (OHC) loss in all turns than nonirradiated ears ( p  <0.05). OHCs were more susceptible to radiation injury than inner HCs in the middle and basal turns ( p  <0.05). In irradiated cochleae, there was a nonsignificant trend for less OHC loss with IT DXM in the basal turn when compared with placebo. IT DXM did not improve radiation-induced hearing threshold shifts; however, a high rate of tympanic membrane perforations occurred with irradiated ears which may contribute to this finding. Conclusion: Radiation induced loss of OHCs in all turns of the cochlea. IT DXM reduced OHC loss in the basal turn of irradiated ears; however, this finding did not achieve statistical significance. Although IT DXM did not affect radiation-induced hearing threshold shifts in adult rats in vivo, this may be due to a high rate of tympanic membrane perforations.